Pemberdayaan Gerakan Masyarakat 4G (Go Green, Go Health, Go Clean dan Go Smart) di UPTD Puskesmas Tangkiling - Elsa Trinovita; Dewi Klarita Furtuna; Silvani Permatasari; Astri Widiarti; Galih Indra Permana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Indonesia is one of the countries set as a corona disaster emergency with the increasing Covid-19 case. One of the factors that caused an increase in Covid-19 cases was the lack of public awareness in implementing 5-M prevention behavior using masks, hand washing using soap and running water, keeping distance, staying away from the crowd, and limiting mobilization and interaction) in his daily life can be a risk transmission in society. Therefore, an approach was carried out in increasing public awareness of the new normal adaptation in the face of the Covid-19 pandemic condition by promoting the